Labor market trends in a low and heterogeneous productivity country. Evidence from Argentina's manufacturing - Graña, Juan Martin (2018)
During Substitution Industrialization (1930-1975), wages rose, and unemployment and poverty were low. During the "neoliberal process" (1976-2002) the liberalization of the goods and financial markets resulted in the regression of the productive structure, high unemployment and the decline of real wages. Finally, since the collapse of 2002, Argentina has had enormous success in terms of unemployment, with limited achievements in wages or poverty. This paper tries to answer why Argentina faces difficulties to return to past labor market figures highlighting the process of capital differentiation and the new international division of labor.